Diffuse Lewy body disease: clinical features in nine cases without coexistent Alzheimer's disease. Issue 5 (May 1996) - Hely, M A; Reid, W G; Halliday, G M; McRitchie, D A; Leicester, J; Joffe, R; Brooks, W; Broe, G A; Morris, J G
Abstract : OBJECTIVE–To further elucidate the relation between diffuse Lewy body disease and Parkinson's disease. METHODS AND RESULTS–The clinical features of nine cases of pure diffuse Lewy body disease without pathological evidence of coexisting Alzheimer's neuritic pathology were reported. All patients were aged less than 70 years at onset (mean 62 years). Five patients presented with clinical features, which included assymetric resting tremor had levodopa responsiveness, which were initially indistinguishable from idiopathic Parkinson's disease. All five patients later became demented (mean of three years after presentation). Two further patients presented with parkinsonism and dementia and two patients presented with dementia and developed parkinsonism at a later stage. Hallucinations appeared 2.5-9 years after the onset of symptoms in six patients and were a presenting feature in one patient. All patients met the pathological criteria of idiopathic Parkinson's disease, with respect to the midbrain changes, in addition to having diffuse cortical Lewy bodies. CONCLUSIONS–Diffuse Lewy body disease may present a parkinsonism, dementia, or both depending on whether the Lewy body pathology begins in the midbrain, the cortex, or both together. When it begins in the midbrain, diffuse Lewy body disease is indistinguishable initially from idiopathic Parkinson's disease. Diffuse Lewy body disease may be a common cause of dementia complicating Parkinson's disease.